Preparation method of graphene-microcrystalline glass

By using graphene dispersion in the preparation of graphene-glass glass for water quenching process, the problem of poor mixing uniformity between graphene and crystallized glass is solved, and the performance and production efficiency of the material are significantly improved.

CN119320239APending Publication Date: 2025-01-17SHANDONG YUHANG PAIMENG NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411386770.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the existing graphene-microcrystalline glass preparation process, the micromorphic form of graphene leads to poor mixing uniformity with other materials, affecting the efficiency of composite materials.

Method used

The graphene dispersion is used to perform the water quenching process of glass melt. Instead of the traditional water quenching liquid, the graphene is evenly distributed in the glass through the water quenching liquid, and heat treatment is carried out under a gas protection atmosphere to form graphene-glass glass Composite material.

Benefits of technology

The uniformity of graphene and microcrystalline glass composite is improved, the performance of the material is enhanced, the process steps are saved, and the production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071128320000061
    Figure BDA0005071128320000061
  • Figure BDA0005071128320000071
    Figure BDA0005071128320000071
Patent Text Reader

Abstract

The invention provides a preparation method of graphene-microcrystalline glass, and relates to the field of graphene-microcrystalline glass composites.The preparation method comprises the following steps that glass powder is molten and then subjected to heat preservation, and molten glass is obtained; the glass melt is subjected to water quenching, a graphene dispersion liquid or a graphene oxide dispersion liquid is adopted as a water quenching liquid, glass residues are taken out after water quenching and dried, and a graphene-microcrystalline glass precursor is obtained; crushing and dispersing the graphene-microcrystalline glass precursor to obtain mixed powder; carrying out tape casting or dry powder tabletting; according to the preparation method disclosed by the invention, the dispersion liquid of the graphene material is used for replacing conventional water in the prior art to serve as a water quenching liquid, so that the compounding uniformity of the graphene and the microcrystalline glass is greatly improved, and the problem of poor compounding uniformity of the graphene and the microcrystalline glass caused by easy agglomeration of the graphene is solved; the synergistic degree of the graphene on the microcrystalline glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of graphene-microcrystalline glass composite materials, and in particular to a method for preparing graphene-microcrystalline glass. Background Art

[0002] With the rapid development of many high-tech technologies, such as information technology and microelectronics, the rapid development of AI technology and the development of computing power technology represented by Chatgpt have put forward higher requirements for the computing power of chips. High-computing chips require higher power, and high power will generate more heat. The development of technology has put forward higher requirements for corresponding materials. Specifically in the field of electronic packaging, packaging materials are mainly used for substrate materials, circuit wiring, component frames, interlayer filling media and sealing. How to improve the heat dissipation and dielectric properties of packaging materials is an industry technical problem that needs to be solved urgently. The preparation of materials with excellent performance and meeting packaging requirements has become the first difficulty to break through in the industry. At present, packaging materials are required to have good sealing performance, low cost, low sintering temperature, good dielectric properties, thermal expansion coefficient matching silicon, and co-firing with conductive metals such as gold, silver and copper.

[0003] Glass-ceramics is a basic glass with a specific composition that is crystallized and heat treated under a certain temperature system, so that a large number of tiny crystals are uniformly precipitated in the glass, thus forming a dense multiphase complex of microcrystalline phase and glass phase. Glass-ceramics has many advantages: the mechanical strength of glass-ceramics is much higher than that of ordinary glass, and even exceeds that of some ceramic materials; it is more ductile than glass and not easy to break; it has higher hardness and good wear resistance; it has good chemical stability and has good resistance to hydration, hydration and cation exchange; it has low dielectric loss rate and is suitable for high-frequency insulation and high-voltage insulation casing materials; it has a low thermal expansion coefficient, good thermal vibration stability, and a high temperature point for high-temperature softening.

[0004] Glass-ceramics is a solid composite material with a crystal phase and a glass phase. As a composite material, glass-ceramics is composed of at least three components: SiO2, Al2O3, and MgO. SiO2, as a glass network former, is an important component of glass formation.

[0005] In the prior art, the patent document with publication number CN107129156A discloses a graphene-microcrystalline glass and a preparation method thereof, which adopts a process of raw material mixing, grinding, molding, and sintering, after graphite powder is evenly mixed with other raw materials, a micromechanical exfoliation method is adopted, and the graphite powder is exfoliated into graphene under the action of external force. After molding and sintering, the graphene sheet is evenly distributed in the structure composed of the microcrystalline glass phase and the glass phase, forming a network-connected nanocomposite structure, and obtaining a graphene-microcrystalline glass with high compressive strength, flexural strength, hardness, and wear resistance.

[0006] The above process is to mechanically peel off the graphite powder in the raw material into graphene during the grinding process, and then blend it with other raw materials. However, since the microscopic morphology of graphene is a flake structure, its surface area is very large and the electrostatic interaction force is large, it is easy to cause agglomeration, which easily leads to poor uniformity in the mixing of graphene and other materials, which is specifically manifested in limited efficiency enhancement of microcrystalline glass. Summary of the invention

[0007] In view of the above problems existing in the prior art, the present invention provides a method for preparing graphene-glass-ceramics.

[0008] The technical solution of the present invention to solve the above technical problems is as follows:

[0009] The present invention provides a method for preparing graphene-glass-ceramics, which is characterized by comprising the following steps:

[0010] S1: Melting the glass powder and keeping it warm to obtain molten glass;

[0011] S2: quenching the glass melt with water, wherein the water quenching liquid is a graphene dispersion or a graphene oxide dispersion, and after the water quenching, removing the glass slag and drying it to obtain a graphene-microcrystalline glass precursor;

[0012] S3: crushing and dispersing the graphene-microcrystalline glass precursor to obtain a mixed powder;

[0013] S4: Cast the mixed powder into a film or dry powder tablet; in addition, punching, filling, screen printing and other process operations can be performed according to the needs of circuit design;

[0014] S5: Heat treatment under a gas protection atmosphere to produce graphene glass-ceramics.

[0015] Furthermore, the mass concentration of the graphene dispersion or graphene oxide dispersion does not exceed 3%, and the flake diameter of the graphene or graphene oxide used is 500nm-40μm.

[0016] Furthermore, the glass powder is composed of the following components by weight: 40-52 parts of SiO2, 18-20 parts of Al2O3, 20-24 parts of MgO, 6 parts of H3BO3, 5-6 parts of CaCO3, 2-6 parts of NaCO3, 3 parts of LiCO3, 3-5 parts of ZrO2, 6-8 parts of TiO2, and 1-2 parts of Y2O3. Among them, MgO, Al2O3, SiO2, H3BO3, CaCO3, NaCO3, and LiCO3 are the base materials of microcrystalline glass, and ZrO2, TiO2, and Y2O3 are composite nucleating agents.

[0017] Furthermore, the glass powder consists of the following components in parts by weight: 52 parts of SiO2, 20 parts of Al2O3, 0 parts of MgO2, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3.

[0018] Furthermore, the melting temperature in step S1 is 1450-1650°C, and the holding temperature is preferably 1350-1500°C.

[0019] Furthermore, the gas protection atmosphere in step S5 is an inert gas, preferably nitrogen or a nitrogen-hydrogen mixed gas with a volume fraction of 5% hydrogen:95% nitrogen.

[0020] Furthermore, the heat treatment temperature in step S5 is not less than 600°C.

[0021] The beneficial effects of the present invention are as follows: the present invention improves the water quenching process of the molten glass in the prior art microcrystalline glass preparation process, specifically, utilizes a dispersion of graphene material instead of conventional water in the prior art as the water quenching liquid, thereby greatly improving the uniformity of the composite of graphene and microcrystalline glass, overcoming the problem of poor composite uniformity with microcrystalline glass due to easy agglomeration of graphene, and improving the degree of enhancement of graphene to microcrystalline glass; at the same time, a water quenching process in this case not only completes the water quenching process itself, but also completes the combination of the molten glass and graphene, saving process steps and facilitating improving production efficiency. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] Example 1

[0024] The preparation of the graphene-glass-ceramics of this embodiment is as follows:

[0025] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; weigh the above materials and ball mill for 2 hours;

[0026] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0027] S3. Water quenching of glass: Graphene with a sheet diameter of 10-20 μm is prepared into a 2% graphene aqueous dispersion; the glass melt is added to the graphene dispersion for water quenching, the glass slag is taken out, dried, crushed, and ground through a 325 mesh sieve to obtain a graphene-microcrystalline glass precursor; the concentration of the graphene dispersion after water quenching is measured, and the difference before and after water quenching, i.e., the water quenching amount m0 ​​of the graphene, is calculated;

[0028] S4. crushing and dispersing the graphene-glass-ceramics precursor to obtain a mixed powder;

[0029] S5. Weigh the mixed powder and press the dry powder into tablets;

[0030] S6. Heat treatment is performed at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, namely graphene microcrystalline glass.

[0031] Example 2

[0032] The preparation of the graphene-glass-ceramics of this embodiment is as follows:

[0033] S1. Raw material preparation: Weigh the following composition by weight: 40 parts of SiO2, 18 parts of Al2O3, 24 parts of MgO, 6 parts of H3BO3, 6 parts of CaCO3, 6 parts of NaCO3, 3 parts of LiCO3, 3 parts of ZrO2, 8 parts of TiO2, and 1 part of Y2O3; weigh the above materials and ball mill for 2 hours;

[0034] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0035] S3. Water quenching of glass: Graphene with a sheet diameter of 10-20 μm is prepared into a 2% graphene aqueous dispersion; the glass melt is added to the graphene dispersion for water quenching, the glass slag is taken out, dried, crushed, and ground through a 325 mesh sieve to obtain a graphene-microcrystalline glass precursor;

[0036] S4. crushing and dispersing the graphene-glass-ceramics precursor to obtain a mixed powder;

[0037] S5. Weigh the mixed powder and press the dry powder into tablets;

[0038] S6. Heat treatment is performed at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, namely graphene microcrystalline glass.

[0039] Example 3

[0040] The preparation of the graphene-glass-ceramics of this embodiment is as follows:

[0041] S1. Raw material preparation: weigh the following composition by weight: 52 parts of SiO2, 18 parts of Al2O3, 24 parts of MgO, 6 parts of H3BO3, 6 parts of CaCO3, 6 parts of NaCO3, 3 parts of LiCO3, 3 parts of ZrO2, 8 parts of TiO2, and 1 part of Y2O3; weigh the above materials and ball mill for 2 hours;

[0042] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0043] S3. Water quenching of glass: Graphene with a sheet diameter of 10-20 μm is prepared into a 2% aqueous dispersion of graphene oxide; the molten glass is added to the graphene dispersion for water quenching, the glass slag is removed, dried, crushed, and ground through a 325 mesh sieve to obtain a graphene-microcrystalline glass precursor;

[0044] S4. crushing and dispersing the graphene-glass-ceramics precursor to obtain a mixed powder;

[0045] S5. Weigh the mixed powder and press the dry powder into tablets;

[0046] S6. Heat treatment is performed at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, namely graphene microcrystalline glass.

[0047] Comparative Example 1

[0048] The preparation method of the graphene-microcrystalline glass in this comparative example is basically the same as that in Example 1, except that water is used as the water quenching liquid in step S3, and the glass powder and graphene obtained after water quenching are mixed by ball milling for subsequent tableting and sintering, specifically:

[0049] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; weigh the above materials and ball mill for 2 hours;

[0050] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0051] S3. Water quenching of glass: adding the molten glass to water for water quenching, removing the glass slag, drying, crushing, grinding through a 325 mesh sieve to obtain a glass fine powder;

[0052] S4. Weighing a graphene powder having a weight of m0, wherein the graphene sheet diameter ranges from about 10 to 20 μm; and ball milling with a glass fine powder for 2 h to obtain a mixed powder;

[0053] S5. Weigh the mixed powder and press the dry powder into tablets;

[0054] S6. Heat treatment is performed at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, namely graphene microcrystalline glass.

[0055] Comparative Example 2

[0056] The preparation method of the graphene-glass-ceramics of this comparative example is basically the same as that of Example 1, except that water is used as the water quenching liquid in step S3, and the glass powder obtained after the water quenching is mixed with the graphene dispersion liquid to obtain a mixture of graphene and glass powder, so as to perform subsequent tableting and sintering, specifically:

[0057] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; weigh the above materials and ball mill for 2 hours;

[0058] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0059] S3. Water quenching of glass: adding the molten glass to water for water quenching, removing the glass slag, drying, crushing, grinding through a 325 mesh sieve to obtain a glass fine powder;

[0060] S4. Weighing a graphene powder having a weight of m0, wherein the graphene sheet diameter ranges from about 10 to 20 μm, preparing a graphene aqueous dispersion, and then uniformly dispersing the glass fine powder therein to obtain a mixture, filtering and drying to obtain a mixed powder;

[0061] S5. Weigh the mixed powder and press the dry powder into tablets;

[0062] S6. Heat treatment is performed at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, namely graphene microcrystalline glass.

[0063] The above embodiments and comparative examples were tested for thermal expansion coefficient, thermal conductivity, dielectric constant, bending strength and other properties, and the test results are shown in Table 1. Among them, the thermal expansion coefficient, thermal conductivity, dielectric constant and bending strength were tested using a thermal expansion coefficient tester, a thermal conductivity tester, a dielectric constant tester and a bending strength universal testing machine, respectively.

[0064] Table 1

[0065]

[0066]

[0067] It can be seen from the data in Table 1 that the embodiment of the present invention adopts graphene aqueous dispersion instead of water quenching liquid in the production process of microcrystalline glass for water quenching. While completing the water quenching in one step, it also forms a combination of glass matrix and graphene. Compared with the control example of first making glass powder and then combining graphene by grinding or combining with graphene dispersion, the scheme of the present invention has more significant effect on the composite material.

Claims

1. A method for preparing graphene-glass-ceramics, characterized in that: The steps include: S1: Melting the glass powder and keeping it warm to obtain molten glass; S2: quenching the glass melt with water, wherein the water quenching liquid is a graphene dispersion or a graphene oxide dispersion, and after the water quenching, removing the glass slag and drying it to obtain a graphene-microcrystalline glass precursor; S3: crushing and dispersing the graphene-microcrystalline glass precursor to obtain a mixed powder; S4: Casting the mixed powder into sheets or pressing dry powder into tablets; S5: Heat treatment under a gas protection atmosphere to produce graphene glass-ceramics.

2. The preparation method according to claim 1, characterized in that: The mass concentration of the graphene dispersion or graphene oxide dispersion does not exceed 3%.

3. The preparation method according to claim 1, characterized in that: The glass powder is composed of the following components by weight: 40-52 parts of SiO2, 18-20 parts of Al2O3, 20-24 parts of MgO, 6 parts of H3BO3, 5-6 parts of CaCO3, 2-6 parts of NaCO3, 3 parts of LiCO3, 3-5 parts of ZrO2, 6-8 parts of TiO2, and 1-2 parts of Y2O3.

4. The preparation method according to claim 3, characterized in that: The glass powder is composed of the following components by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3.

5. The preparation method according to claim 3, characterized in that: The melting temperature in step S1 is between 1450°C and 1650°C.

6. The preparation method according to claim 1, characterized in that: The gas protection atmosphere in step S5 is an inert gas.

7. The preparation method according to claim 6, characterized in that: The gas protection atmosphere in step S5 is nitrogen or a nitrogen-hydrogen mixed gas with a volume fraction of 5% hydrogen:95% nitrogen.

8. The preparation method according to claim 1, characterized in that: The heat treatment temperature in step S5 is not less than 600°C.

Citation Information

Patent Citations

  • Graphene-microcrystal glass and preparation method thereof

    CN107129156A